ANALISIS KARAKTER TOKOH DALAM NOVEL SI ANAK BADAI KARYA TERE LIYE - Teresia Alwandra Nanda; Sesilia Seli; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the characters contained in the novel Si Anak Badai by TereLiye, to describe some of the characters in the novel and to find out the character implementation of the characters in the Indonesian language learning process at the SMA / MA level. The method used is descriptive method with a qualitative research form. The ap proach used is a structuralism approach. The data source of this research is the novel SiAnak Badai by Tere Liye. The data collection techniques and tools used in this research were documentary studies and the researchers themselves. The technique of testing the validity of the data used observation persistence, triangulation and reference adequacy. The results of this research are about the characters contained in the novel Si Anak Badai by Tere Liye which are owned by several characters who play an active role in the novel, namely the characters who play an active role, namely the main characters include Zaenal characters and supporting character characters including the characters Awang, Malim, Ode, Pak Kapten. or Sakai bin Manaf, teacher Rudi, Fatma Ibu Zaenal, Zul Mr. Zaenal, Bu Rum, Pak Alexander, and the head of the Tiong sub-district. The implementation of character characters contained in the novel for learning Indonesian seen from the aspects of the curriculum, learning objectives, selection of teaching materials, and the level of readability are appropriate as learning materials for students of class XII SMA / MA.Keywords: novel, character, structuralism approach.